PENGARUH LINGKUNGAN FISIK DAN SETTING MOUSE TERHADAP AKURASI MENEMBAK GAME FIRST PERSON SHOOTER - Sukwadi, Ronald; Damasputra, Albertus Nugi Prasetya; Silalahi, Agustinus; Prasetya, Wibawa; Silitonga, Riana Magdalena (Universitas Putera Batam, 2024)
The First-Person Shooter (FPS) game genre has gained significant popularity in the e-sports industry during 2022-2023. This study investigates the impact of physical environment and mouse settings on shooting accuracy in FPS gameplay. Participants were divided into beginner and advanced groups based on experience and playtime, or “flight hours.” Key variables include environmental factors—such as lighting and room temperature—and mouse settings, including mouse weight and DPI. Experiments were conducted using the AimLab application, with ANOVA and ANOM statistical tests used to determine optimal conditions. For advanced players, the ideal settings were identified as a room temperature of 16°C, no lighting, and a mouse weight of 100 grams. For beginners, the optimal condition was a room temperature of 16°C.